1983
DOI: 10.1007/bf00020156
|View full text |Cite
|
Sign up to set email alerts
|

Why do cracks avoid each other?

Abstract: The experimentally known phenomenon that originally collinear mode I cracks seem to avoid each other before coalescence is studied by investigating the stability of straight crack paths. To this end a periodic array of approximately collinear but slightly curved cracks is considered. Stress intensity factors for modes I and II are derived and the growth of originally straight cracks under mode I conditions is studied after introduction of a disturbance that forces the cracks to deviate from a straight path. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
51
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(60 citation statements)
references
References 4 publications
9
51
0
Order By: Relevance
“…It has also been shown that two collinear approaching cracks (submitted to a uniaxial stress in mode I) can repel each other instead of merging tip to tip [21], resulting in a curved, "hookshaped" path. Such cracks have been observed for a wide range of scales in nature, from 25 cm quartz-feldspar veins in granite to 25 km-long oceanic ridges [18], as well as in laboratory experiments on glass [22], Polymethylmethacrylate plates [21,23] or more recently in paper [24] and gelatin sheets [25]. Theoretical studies have tried to explain this truly nonintuitive behavior.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…It has also been shown that two collinear approaching cracks (submitted to a uniaxial stress in mode I) can repel each other instead of merging tip to tip [21], resulting in a curved, "hookshaped" path. Such cracks have been observed for a wide range of scales in nature, from 25 cm quartz-feldspar veins in granite to 25 km-long oceanic ridges [18], as well as in laboratory experiments on glass [22], Polymethylmethacrylate plates [21,23] or more recently in paper [24] and gelatin sheets [25]. Theoretical studies have tried to explain this truly nonintuitive behavior.…”
mentioning
confidence: 96%
“…Theoretical studies have tried to explain this truly nonintuitive behavior. First, Melin [23] showed that the collinear crack configuration is unstable. Then, Kachanov [26] noticed that the slightest disturbances in the initial symmetric configuration will give rise to a mixed mode interaction (traction and shear stresses).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus unlike the opening mode crack problems, the lengthening of the LVRSs appears to have inherent limitation. Also, it is well known that originally collinear mode I crack tips would avoid each other before coalescence and thus tip-to-tip coalescence would not take place [Melin, 1983]. However, our simulation results, based on the volumetric plastic strain distributions around PSSs' tips, appear to show that two neighboring collinear or echelon PSSs are able to link directly from tip to tip if their closer tips distance is relatively small.…”
Section: Interpretation and Discussionmentioning
confidence: 63%
“…on a branched crack on an aircraft wheel rim made of 2014-T6 aluminum alloy [4]. Some analytical solutions have been obtained for the SIF of kinked and branched cracks, but it is generally recognized that it is very difficult to develop accurate analytical solutions to their complex propagation behavior [5][6][7][8][9]. Therefore, numerical methods such as Finite Elements (FE) and Boundary Elements (BE) are the only practical means to predict the propagation behavior of branched cracks [10].…”
Section: Introductionmentioning
confidence: 99%